Proposals for the development of information-measuring systems for control of the technical condition of samples of special equipment / О. Іоhоv, S. Tymchenko // Application of information technologies in the preparation and operation of law enforcement forces : Collection of theses of reports of International scientific and practical conference, March 15, 2022. – Kharkiv. – 2022. – p. 32-33. - Іоhоv, О.; Tymchenko, S. (National Academy of the National Guard of Ukraine, 2022)
The implementation of the measures outlined in the report will allow the development of modern information and measuring systems to monitor the technical condition of samples of special equipment.
Keywords: information-measuring systems for control; technical condition